Association between risky behaviors in adolescents and altered psychophysiological emotional responses - Galindo Aldana, Gilberto Manuel; Fraga Vallejo, Miguel; Menchaca Díaz, Rufino; Alvelais-Alarcón, Marina; Machinskaya, Regina (My University, 2017)
Introduction: The psychophysiology of emotional response in adolescence is a crucial factor for understanding risk and deviant behaviors. Objective: To compare specific characteristics of psychophysiological emotional response between risk behavior adolescents and controls. Materials and methods: Characterization of risk behaviors (RB), variations in the heart rate (HR), electromyography (EMG), skin conductance (SC) and temperature during the presentation of visual emotional stimuli. The emotional valence parameters, activation and dominance of such stimuli were qualified as well. Results: Significant differences were found among RB adolescents compared to the non-risk group, as well as signs of major psychophysiological response to emotionally loaded stimuli in RB when compared to the control group. The control group was characterized by initial bradycardia, which was more evident than in the risk behavior group. Conclusions: The control group presented more expressive initial bradycardia in comparison to the RB group. Both groups showed more pronounced cardiac deceleration when experiencing unpleasant stimuli, higher levels in EMG to pleasant stimuli in the RB group, and higher CP indicators for the three types of stimulus. A cohort study is required in order to compare current findings in RB versus physiological emotional response among adolescent groups.
Revista de la Facultad de Medicina
Keywords: Risk behavior; Psychophysiological; Reaction; Adolescence; Sistemas